PERANCANGAN & PRODUKSI SHORT COURSE MEBEL MELALUI KOKREASI BERSAMA PENGRAJIN MEBEL INDUSTRI - Hartanto, Susi (JUARA: Jurnal Wahana Abdimas Sejahtera, 2025)
The furniture manufacturing industry affected by the pandemic has stopped working or reduced the working days / hours of craftsmen, so that the income of craftsmen is lost or reduced. During online lectures, students have problems understanding the practical learning of furniture production. This community service program provides solutions to the 2 problems above by channeling the skills of furniture craftsmen into short courses, which can later be accessed by students or high school students. There are 3 parties working here: UPH, furniture craftsmen, and industrial partners. UPH as the organizer of community service program, furniture craftsmen as subjects of community service program, and industrial partners as sponsors of equipment and venue loans. Through this first period of community service program, the UPH team aims to: 1) help furniture craftsmen affected by the pandemic earn additional income by channeling their skills through short courses; 2) provide learning materials for students about the practice of making various kinds of furniture that are comprehensive directly from expert craftsmen; 3) produce short courses that can be sold as non-academic revenue for study programs, or as after school activities for high school activities that are useful for promotional activities. This period is the first period of the community scheme which is prepared for 5 years, as a form of study program support for the university's initiative to run blended learning full curriculum integration and talent development. The result is a set of instructional videos on the making of a scaled dining chair, ready to be uploaded as material for a short course.